The death of a Confederate : selections from the letters of the Archibald Smith family of Roswell, Georgia, 1864-1956 - Skinner, Arthur N.; Skinner, James L., 1938- (University of Georgia Press, 1996)
The letters cover William and Archibald Smith's service in the Confederate armies at Savannah and in the Carolinas ; the family fleeing Sherman's advance, William's death shortly after the war, life under Reconstruction, and how subsequent generations remembered the war years. Included is a very brief description of an 1899 reunion of Confederate veterans at the Citadel.